2015
DOI: 10.1089/eco.2014.0058
|View full text |Cite
|
Sign up to set email alerts
|

The Well-Being of Allotment Gardeners: A Mixed Methodological Study

Abstract: ). AbstractPurpose: The potential for 'green' interventions to promote mental wellbeing and reduce mental distress is increasingly being recognised. Preliminary evidence suggests that allotment gardening activities may have a significant effect on mental wellbeing, but a need for further research has been highlighted. This study investigated the relationships between allotment gardening, feeling connected to nature and wellbeing.Design: A mixed methods design was utilized. Measures of subjective wellbeing (qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…There is evidence that NC mediates the relationship between exposure to nature and EWB (Mayer et al 2009;Pensini et al 2016;Webber et al 2015), which would be consistent with a causal mechanism whereby nature exposure leads to increased NC, which in turn leads to improved EWB. However, another study has found that NC does not moderate the effect of nature exposure on EWB (as measured by elevating experience) (Passmore and Howell 2014), which implies that NC may not play a part in promoting EWB.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…There is evidence that NC mediates the relationship between exposure to nature and EWB (Mayer et al 2009;Pensini et al 2016;Webber et al 2015), which would be consistent with a causal mechanism whereby nature exposure leads to increased NC, which in turn leads to improved EWB. However, another study has found that NC does not moderate the effect of nature exposure on EWB (as measured by elevating experience) (Passmore and Howell 2014), which implies that NC may not play a part in promoting EWB.…”
Section: Discussionmentioning
confidence: 82%
“…Correlational studies have shown that NC is associated with a variety of eudaimonic well-being indicators, such as autonomy, vitality, meaning, and personal growth (Cervinka et al 2012;Nisbet and Zelenski 2013;Pensini et al 2016), as well as with hedonic wellbeing (Capaldi et al 2014). There is some evidence that NC may mediate the relationship between exposure to nature and well-being (Mayer et al 2009;Webber et al 2015;Pensini et al 2016), but the evidence is not consistent as other studies have found that NC does not influence the relationship between nature exposure and wellbeing (Passmore and Howell 2014; Passmore and Holder 2017).…”
Section: Nature Connectednessmentioning
confidence: 99%
“…There is a growing ecopsychology movement in Europe, based on the principle that this human connection to the earth is vital, both for the wellbeing of individuals and the survival of the planet (see Burls, 2007). Furthermore, recent quantitative research found that connectedness to nature mediated the positive relationship between time spent on the allotment and eudemonic wellbeing (Webber et al, 2015).…”
Section: Theme 2: Physical and Mental Protectionmentioning
confidence: 99%
“…The researchers identified a need for further research into the public health potential of everyday allotment gardening. One subsequent study explored the relationship between allotment gardening and wellbeing through an online survey of 171 UK allotment gardeners (Webber, Hinds, & Camic, 2015). The findings indicated that time spent on the allotment is positively associated with eudemonic wellbeing (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There is additional evidence suggesting that several therapeutic goals, such as interaction levels and self-esteem, can be achieved by gardening activities (Rappe et al, 2008). These may have a positive role in the longer-term management of mental health, with 'green' interventions increasingly recognised in the promotion of well-being (Webber et al, 2015).…”
Section: Studies Of the Use Of Green Spaces In Mental Healthcarementioning
confidence: 99%